2019
DOI: 10.4103/apjon.apjon_37_18
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Spiritual Care for Cancer Patients and Oncology Nurses: a Qualitative Study

Abstract: Objective: The nature of cancer increases the spiritual needs of patients and necessitates the provision of holistic care for them. By trying to meet the spiritual needs of patients, oncology nurses can help them adapt, gain inner peace, and develop positive thoughts and attitudes. This study aimed to explore the consequences of spiritual care for cancer patients and oncology nurses from the perspective of the patients, family members, nurses, and other health-care team members. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
11
1
2
Order By: Relevance
“…Outro estudo relaciona a religiosidade e a espiritualidade aos profissionais de saúde. O cuidado espiritual de pacientes com câncer coloca o doente e até a enfermeira oncológica no caminho para o desenvolvimento espiritual, que ajuda na promoção do conforto, da sensação de paz e da satisfação interior, que auxiliam no tratamento da doença 43 . Esse processo de cuidado deve ser planejado para fornecer necessidades e práticas espirituais entre os cuidadores e os familiares de pacientes com câncer 44 .…”
Section: Discussionunclassified
“…Outro estudo relaciona a religiosidade e a espiritualidade aos profissionais de saúde. O cuidado espiritual de pacientes com câncer coloca o doente e até a enfermeira oncológica no caminho para o desenvolvimento espiritual, que ajuda na promoção do conforto, da sensação de paz e da satisfação interior, que auxiliam no tratamento da doença 43 . Esse processo de cuidado deve ser planejado para fornecer necessidades e práticas espirituais entre os cuidadores e os familiares de pacientes com câncer 44 .…”
Section: Discussionunclassified
“…Further attention to these domains enables a spiritually nurturing environment, meaning-centred therapeutic interventions, patient-centeredness, an exploration of the spiritual perspective, spiritual aspects of nurses' reasoning and processes, and the quality of expertise (van Leeuwen & Cusveller 2004; Ramezani et al 2014). In this regard, the authors of this article also found that empathy and genuine attention to patients' needs, adequate information and therapeutic presence are foundational to developing compassionate relationships (Rochmawati & Minanton 2020).Patients with cancer expect nurses to attend to their spiritual needs which allows them to achieve a sense of peace, comfort and inner satisfaction (Moosavi et al 2019). The authors also found that nurse-patient-relative communication in cancer care often includes addressing spirituality and…”
mentioning
confidence: 93%
“…Patients with cancer expect nurses to attend to their spiritual needs which allows them to achieve a sense of peace, comfort and inner satisfaction (Moosavi et al 2019). The authors also found that nurse-patient-relative communication in cancer care often includes addressing spirituality and…”
mentioning
confidence: 99%
“…21 Incorporating spirituality is one strategy to culturally tailor interventions for faith-based communities and has been effective for health behavior change in underserved populations. 16 Spirituality is defined by some researchers as “the way a person searches for meaning and purpose in life, as well as the relationship between himself and others, nature, and the sacred,” 22 or can more simply refer to feelings of peace, meaning, and purpose in life. Culturally-tailored, spiritualty-based interventions have shown promising results for improving mental health outcomes, such as stress, depression, and anxiety.…”
Section: Introductionmentioning
confidence: 99%